El crecimiento poblacional: una propuesta pedagógica para abordar Biología, Matemáticas y TICs. - AGUINALDO ROBINSON DE SOUZA; DIANA MORENO SIERRA; JAIRO GONÇALVES CARLOS (Universidad Distrital Francisco José de Caldas, 2010)
In this paper we propose the achievement of an interdisciplinary activity evolving biology and mathematics knowledge with students of the third grade of high school about the population growth theme. The goal of this activity is to offer to the students a wider perception about the ways of population growth of different organisms from their home region, helping them to represent it through mathematics models. The formulation of the research problem is done from the theoretical and empirical data and the student is encouraged to behave in a participative and dialogic way in all stages of the activity. The mathematical modeling and the graphic representation of the population growth are made through the mathematical software Geogebra and we emphasize the qualitative analysis of the data from the Biological and environmental education point of view.